Role of shortwave and microwave diathermy in peripheral neuropathy. Issue 8 (August 2019) - Fu, Tengfei; Lineaweaver, William C.; Zhang, Feng; Zhang, Jian
Objective: This study was performed to review the current evidence for the efficacy of shortwave and microwave diathermy in promoting nerve regeneration after peripheral nerve injuries in both animal models and human patients. Methods: An extensive literature search was conducted without publication data restrictions. Studies including the intervention and outcome in animal or human models were selected. Non-English studies, reviews, letters, and case reports were excluded. Results: Eleven articles were included in this study. Shortwave diathermy at the frequency of 27.12 or 40.68 MHz was used in six of seven animal studies, while only one study utilized microwave diathermy at 915 MHz. Seven animal experiments demonstrated that shortwave or microwave diathermy produces an increased myelinated nerve fiber number, myelin sheath thickness, and axon diameter as well as improved electrophysiological parameters and locomotion. A total of 128 patients (207 wrists) were enrolled in four clinical studies. The clinical use of diathermy in human patients with carpal tunnel syndrome showed positive effects on pain, hand function, and electrophysiological findings. Conclusions: Shortwave or microwave diathermy can improve the electrophysiological parameters, myelinated fiber number, and axon diameter of the injured nerve.